Creating “Good” Thai Citizens: Religions in Thai Textbooks - Yavaprabhas, Kakanang (Journal of Mekong Societies, 2022)
Religions form part of the content in textbooks and are typically seen as standard knowledge. This study examines how religions appear in Thai textbooks, an important but relatively unexplored topic of study. Using an anthropological approach to textbooks and critical discourse analysis, I analyze 42 textbooks of primary school levels that are used for three subjects. I propose that there are three main discourses formed by religions: discourses about us and others; about goodness; and about Buddhism, Thai-ness, and the Thai state. I argue that these discourses show how the Thai state uses religions in the hope of creating desirable “good” citizens, while simultaneously stigmatizing those who fail to conform.